PENGARUH KEMISKINAN, PERTUMBUHAN EKONOMI, DAN PENGELUARAN PEMERINTAH TERHADAP KEMISKINAN DI KALIMANTAN TIMUR - Reynaldi Alviano; Ida Nuraini; Hendra Kusuma (Jurnal Ilmu Ekonomi, 2020)
In the province of East Kalimantan, poverty is a problem that still cannot be overcome. Poverty in the province of East Kalimantan from year to year is still high, which is not in line with economic growth which is also high in East Kalimantan compared to other Kalimantan Provinces. Poverty is high due to unemployment which is also high and government spending also affects poverty in East Kalimantan. The purpose of this research is to determine the effect of unemployment, economic growth, and government spending on poverty in East Kalimantan Province. The data used are secondary data derived from the statistical body (bps) of East Kalimantan and odjk of the finance ministry. The method of analysis uses panel data analysis and fixed-effect models. The results of this study indicate that simultaneous unemployment, economic growth, and government spending affect poverty in East Kalimantan Province. The unemployment variable has a positive and significant effect on poverty, the economic growth variable has a negative and significant effect on poverty, while the government expenditure variable has a negative and significant effect on poverty in East Kalimantan